Efficient production of glutathione in Saccharomyces cerevisiae via a synthetic isozyme system. Issue 1 (14th November 2022) - Jeon, Gi‐Beom; Lee, Hyun‐Jae; Park, Jong Pil; Park, Kyeongsoon; Choi, Chang‐Hyung; Kim, Sun‐Ki
Abstract: Glutathione, a tripeptide consisting of cysteine, glutamic acid, and glycine, has multiple beneficial effects on human health. Previous studies have focused on producing glutathione in Saccharomyces cerevisiae by overexpressing γ‐glutamylcysteine synthetase (GSH1) and glutathione synthetase (GSH2), which are the rate‐limiting enzymes involved in the glutathione biosynthetic pathway. However, the production yield and titer of glutathione remain low due to the feedback inhibition on GSH1. To overcome this limitation, a synthetic isozyme system consisting of a novel bifunctional enzyme (GshF) from Gram‐positive bacteria possessing both GSH1 and GSH2 activities, in addition to GSH1/GSH2, was introduced into S. cerevisiae, as GshF is insensitive to feedback inhibition. Given the HSP60 chaperonin system mismatch between bacteria and S. cerevisiae, co‐expression of Group‐I HSP60 chaperonins (GroEL and GroES) from Escherichia coli was required for functional expression of GshF. Among various strains constructed in this study, the SKSC222 strain capable of synthesizing glutathione with the synthetic isozyme system produced 240 mg L ‐1 glutathione with glutathione content and yield of 4.3% and 25.6 mgglutathione /gglucose, respectively. These values were 6.6‐, 4.9‐, and 4.3‐fold higher than the corresponding values of the wild‐type strain. In a glucose‐limited fed‐batch fermentation, the SKSC222 strain produced 2.0 g L ‐1 glutathione in 67 h. Therefore, this study highlights the benefits of the synthetic isozyme system in enhancing the production titer and yield of value‐added chemicals by engineered strains of S. cerevisiae . Graphical Abstract and Lay Summary: GARAPHICAL ABSTRACT: Glutathione, a tripeptide consisting of cysteine, glutamic acid, and glycine, has multiple beneficial effects on human health. This study highlights the benefits of the synthetic isozyme system to enhance the production titer and yield of glutathione by engineered strains of Saccharomyces cerevisiae . In addition, the synthetic isozyme system used in this study can be applied to the production of other functional molecules.